The First of All Sacraments: Compadrazgo and Slavery in an Exporting Village (Castro, Captaincy of São Paulo, c.1789-1836) - Assis, Vinícius Augusto Andrade de (Revista Crítica Histórica, 2022)
Parish baptism records allow for an in-depth analysis of questions about demographic variables, political geography by preferential godparents, the legal status or social quality of registered subjects, strategies, and choices in the godparent relationship, in order to recognize the hierarchies in a slave society molded in the values of the Ancien Régime. Starting from the nominative crossing of sources, I propose to discuss slavery and cronyism in the São Paulo village of Castro, varying the observation scales between the parish and two specific farms. In dialogue with historiography and understanding that general patterns are products of specific combinations of cronyism, I consider the conciliation between quantitative data and microanalysis as an important tool, since it allows the visualization of social complexity in a non-exporting locality.